THE INFLUENCE OF INTEREST AND MOTIVATION ON STUDENT LEARNING OUTCOMES IN FIQH SUBJECTS AT MAN 2 PALEMBANG - Ermis Suryana; Ari Sandi; Elhefni Elhefni (Conciencia, 2022)
This study aims to analyze the effect of interest in learning and learning motivation on student learning outcomes in Fiqh subjects after the Covid-19 pandemic in class XI MIPA 1 MAN 2 Palembang. This study used quantitative research methods, with a population of 37 respondents, and made a research sample using convenience sampling techniques, the data collection techniques used were questionnaires and tests, then analyzed by simple linear regression and multiple linear regression hypothesis tests. Based on the results of simple linear regression hypothesis analysis, student interest in learning obtained a value of R = 0.257. While the contribution contributed by student interest in learning (X1 ), to student learning outcomes (Y) = 0.066 = 6.6%, Furthermore, student learning motivation obtained a value of R = 0.149. While the contribution contributed by student learning motivation (X2 ), to student learning outcomes (Y) amounted to = 0.022 = 2.2%, this shows that student interest in learning and student learning motivation there is a positive and significant influence. The meaning of positive and significant is that between the variables of student interest in learning (X1) and student learning outcomes (Y) are unidirectional, the meaning of unidirectional here is that the more student interest in learning (X1) increases, the more student learning outcomes (Y) increase, on student learning outcomes in Fiqh subjects after the Covid-19 pandemic in class XI MIPA 1 MAN 2 Palembang. Then the results of the multiple linear regression hypothesis analysis obtained a value of R = 0.0.318. Contributions made by Both of these variables on the variable (Y) amounted to = 10.1%, it can be concluded that, there is a positive and significant influence together (simultaneously) between student learning interest (X1) and student learning motivation (X2 ) on student learning outcomes (Y) in Fiqh subjects in class XI MIPA 1 MAN 2 Palembang.